Development of the Japanese version of the State Behavioral Scale for critically ill children. Issue 2 (21st December 2018) - Hoshino, Haruhiko; Sakuramoto, Hideaki; Matsuishi, Yujiro; Shimojo, Nobutake; Enomoto, Yuki; Ohto, Tatsuyuki; Kido, Takahiro; Ouchi, Akira; Sumitani, Masahiko; Kawano, Satoru; Inoue, Yoshiaki
Abstract : Aims: The State Behavioral Scale (SBS) was developed to assess sedation states, including agitation, in pediatric patients on mechanical ventilation. The purpose of this study was to determine the reliability and validity of a back‐translated Japanese version of the SBS. Methods: Translation was done by the back‐translation method followed by a prospective study in a Japanese intensive care unit. For reliability, a nurse/researcher pair evaluated SBS along eight dimensions (respiratory drive, response to ventilation, coughing, best response to stimulation, attentiveness to care provider, tolerance to care, consolability, and movement after consoled). For validity, SBS scores were compared to the Richmond Agitation–Sedation Scale and a visual analog scale (VAS). Results: The original author approved the back‐translated SBS. Thirty‐one patients aged 0 weeks to 8 years were evaluated from 59 total critical pediatric patient encounters. The researcher and nurse SBS scores demonstrated excellent inter‐rater reliability (weighted κ = 0.96, 95% CI 0.92–0.99). In addition, there was a very strong correlation between the researcher and nurse VAS scores (ρ = 0.80, P < 0.001). Weighted kappa coefficients for the eight dimensions ranged from 0.71 (95% confidence interval, 0.55–0.88; consolability) to 0.89 (95% confidence interval, 0.80–0.98; best response to stimulation). In validity testing, nurse SBS and nurse VAS scores were strongly correlated (ρ = 0.80, P < 0.001) with the researcher SBS and researcher Richmond Agitation–Sedation Scale scores (ρ = 0.91, P < 0.001). Conclusion: This study suggests that our Japanese version of the SBS is valid and reliable for evaluating sedation for critically ill children. Abstract : The purpose of this study was to determine the reliability and validity of a back‐translated Japanese version of the State Behavioral Scale (SBS). The Japanese version of the nurse SBS and nurse visual analog scale scores were strongly correlated (ρ = 0.80, P < 0.001), and the researcher and nurse SBS scores showed excellent inter‐rater reliability (weighted κ = 0.96; 95% confidence interval, 0.92–0.99). We developed the Japanese version of the SBS.